DIMENSIONS OF A MATURITY MODEL FOR INFORMATION SYSTEMS IN HIGHER EDUCATION INSTITUTIONS - Rui Humberto Pereira (2021)
The complexity of the information systems (IS) in the higher education institutions (HEI) has been continuously increasing during the last decades. Thus, managers need tools to evaluate the maturity of their IS, in order to continuously improve them. Additionally, the accreditation processes and rankings may also include organisational aspects in their criteria, in which the maturity models may be a useful tool. However, the existing literature is scarce on validated maturity models focused on the comprehensive management of complex HEI information systems. In previous papers, we came to the conclusion of the need and opportunity to propose a new maturity model to evaluate the IS of HEI, as well as the methodology to follow in the development of such model. In the present paper, we discuss our proposal for the architecture of the new model, synthetizing the state of the model that we intend to develop. This proposal is based on a two-dimensional approach, composed by vertical and horizontal dimensions of information. We believe that our approach, can mitigate the implications of the complexly issues of HEI on the maturity model to be developed. This proposal it the result of a multicase study, in which we identified the dimensions to consider in the model. In the further steps of our work, we will validate each of one of these dimensions and define the set of characteristics for each stage of maturity. Keywords: Stages of Growth, Maturity Models, Higher Education Institutions, Education Information Systems, Management.